Evaluation of Students’ Perception of E-Learning Education Atmosphere (EEAM) in a Private Dental College in Pakistan - Akbar, Zainab; Gul, Khaula; Nasir, Falahat; Hameed, Waqas; Durrani, Mushyyada; Ullah, Hidayat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the e-learning educational environment of our institute using a tool called the E-learning educational atmosphere measure (EEAM).Study design: Cross-sectional study.Place and Duration of Study: Rehman College of Dentistry, Peshawar Pakistan, from Oct 2020 to Mar 2021.Methodology: A pre-validated EEAM questionnaire comprising seven domains was used as a data collection tool. The questionnaire was distributed among all the Rehman College of Dentistry students, Peshawar and the response was obtained. All questions were assessed on a five-point Likert scale ranging between one and five.Results: A total of 161 students were included, with a response rate of 80.1%. The mean age of the students was 21.54±1.38 years, (range: 21-23 years). Responses to questions of all first five domains of awareness of rules, safety and convenience, teaching quality, learner support, ethics, and professionalism mostly were towards agreement and strongly agreement side. The responses to questions 41 and 42 of the program effectiveness domain and 44 and 45 of the knowledge, affective and psychomotor domain were mainly towards the disagreement side.Conclusion: The colleges should concentrate on introducing new strategies to improvise the program's effectiveness along with better teaching of affective and psychomotor skills. They should target the senior classes and the female tutees by educating them about the pros and cons of online learning and its dynamics to achieve better outcomes and results.